2012
DOI: 10.1258/ebm.2011.011294
|View full text |Cite
|
Sign up to set email alerts
|

In vitromodels for gluten toxicity: relevance for celiac disease pathogenesis and development of novel treatment options

Abstract: In genetically predisposed individuals, dietary gluten in wheat, rye and barley triggers celiac disease, a systemic autoimmune disorder hallmarked by an extensive small-bowel mucosal immune response. The current conception of celiac disease pathogenesis is that it involves components of both innate and adaptive immunity whose activation typically leads to small-bowel villous atrophy with crypt hyperplasia. Currently, the only effective treatment for celiac disease is a strict lifelong gluten-free diet excludin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 95 publications
(101 reference statements)
0
18
0
2
Order By: Relevance
“…Lastly, the in vitro results using the Caco-2 cell model, widely adopted in CD studies [58,59] and challenged with a direct digested gliadin administration, provided a possible mechanistic view of the regulatory effects of miRNAs, specifically miR-17, on the expression of a key autophagic gene as ATG7 . Similar to our previous results [29], we showed that even only modulating intracellular miR-17 levels, this can significantly alter the autophagic status of the cells.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the in vitro results using the Caco-2 cell model, widely adopted in CD studies [58,59] and challenged with a direct digested gliadin administration, provided a possible mechanistic view of the regulatory effects of miRNAs, specifically miR-17, on the expression of a key autophagic gene as ATG7 . Similar to our previous results [29], we showed that even only modulating intracellular miR-17 levels, this can significantly alter the autophagic status of the cells.…”
Section: Discussionmentioning
confidence: 99%
“…Ex-vivo gluten application on gluten-free diet intestinal biopsy, bypass the obstacle. Many ex-vivo, in vitro models were described, using human originated intestinal cell-lines or CD patients small bowel mucosal biopsies [41,42]. We know nowadays that gluten or gliadin, when incubated with primary cultures of CD patients on glutenfree diet,induces morphological as well as immunological aberrations.…”
Section: Discussionmentioning
confidence: 99%
“…To detect the antigenic properties of gliadin peptides, in vitro challenge of CD patients' PBMCs (55), small intestinal biopsies (31), and gluten-specific T cell lines generated from biopsies (35,38) have been employed. In our study we employed PBMCs.…”
Section: Discussionmentioning
confidence: 99%